Предмет: Алгебра, автор: wintercrow49

даю 15 баллов за все

Приложения:

Ответы

Автор ответа: YYarr
0

1) \left \{ {{x+y=3} \atop {x-y=7}} \right.

\left \{ {{x+y=3} \atop {x=y+7}} \right.

\left \{ {{y+7 +y=3} \atop {x=y+7}} \right.

\left \{ {{2y= -4} \atop {x=y+7}} \right.

\left \{ {{y=-2} \atop {x=y+7}} \right.

\left \{ {{y=-2} \atop {x=-2+7}} \right.

\left \{ {{y=-2} \atop {x=5}} \right.

2)\left \{ {{5x-6y=7} \atop {10x+6y=8}} \right.

\left \{ {{5x - 6y = 7} \atop { 6y=8-10x}} \right.

\left \{ {{5x-(8-10x)=7} \atop {6y=8-10x}} \right.

\left \{ {{x=1} \atop {6y=8-10*1}} \right.

\left \{ {{x=1} \atop {y=-\frac{1}{3} }} \right.

3) \left \{ {{5x+4y=25} \atop {5x-3y=-3}} \right.

\left \{ {{5x+4y=25} \atop {5x=-3+3y}} \right.

\left \{ {{-3+3y+4y=25} \atop {5x=-3+3y}} \right.

\left \{ {{y=4} \atop {5x=-3+3y}} \right.

\left \{ {{y=4} \atop {x=\frac{9}{5} }} \right.

4)\left \{ {{y=4-3x} \atop {5x-2y=14}} \right.

\left \{ {{y=4-3x} \atop {5x-2(4-3x) = 14}} \right.

\left \{ {{y=4-3x} \atop {x=2}} \right.

\left \{ {{y=4-3*2} \atop {x=2}} \right.

\left \{ {{y=-2} \atop {x=2}} \right.

Автор ответа: e71154718
0

Ответ:

{

6y=8−10∗1

x=1

{

=

1

=

1

3

{

y=−

3

1

x=1

3)

{

5

+

4

=

25

5

3

=

3

{

5x−3y=−3

5x+4y=25

{

5

+

4

=

25

5

=

3

+

3

{

5x=−3+3y

5x+4y=25

{

3

+

3

+

4

=

25

5

=

3

+

3

{

5x=−3+3y

−3+3y+4y=25

{

=

4

5

=

3

+

3

{

5x=−3+3y

y=4

{

=

4

=

9

5

{

x=

5

9

y=4

4)

{

=

4

3

5

2

=

14

{

5x−2y=14

y=4−3x

{

=

4

3

5

2

(

4

3

)

=

14

{

5x−2(4−3x)=14

y=4−3x

{

=

4

3

=

2

{

x=2

y=4−3x

{

=

4

3

2

=

2

{

x=2

y=4−3∗2

{

=

2

=

2

{

x=2

y=−2

1{

6y=8−10∗1

x=1

{

=

1

=

1

3

{

y=−

3

1

x=1

3)

{

5

+

4

=

25

5

3

=

3

{

5x−3y=−3

5x+4y=25

{

5

+

4

=

25

5

=

3

+

3

{

5x=−3+3y

5x+4y=25

{

3

+

3

+

4

=

25

5

=

3

+

3

{

5x=−3+3y

−3+3y+4y=25

{

=

4

5

=

3

+

3

{

5x=−3+3y

y=4

{

=

4

=

9

5

{

x=

5

9

y=4

4)

{

=

4

3

5

2

=

14

{

5x−2y=14

y=4−3x

{

=

4

3

5

2

(

4

3

)

=

14

{

5x−2(4−3x)=14

y=4−3x

{

=

4

3

=

2

{

x=2

y=4−3x

{

=

4

3

2

=

2

{

x=2

y=4−3∗2

{

=

2

=

2

{

x=2

y=−2

Похожие вопросы